SOSIAL SUPORT GURU BIMBINGAN DAN KONSELING UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR - Lopen, L Leonotus; Wibowo, Satrio Budi; Mudaim, Mudaim (Counseling Milenial (CM), 2023)
Learning discipline is an attitude or behavior to be able to carry out their obligations to learn, both studying at school and studying at home. The purpose of this study was "to find out how the form of social support carried out by Guidance and Counseling teachers in improving the learning discipline of students of SMA Negeri 1 Punggur". This research was a qualitative research where the implementation of this research was to find out the form of support provided by Guidance and Counseling teachers in improving the learning discipline for students of SMA Negeri 1 Punggur in the 2018/2019 academic year. Collecting data used interview techniques (1) BK teachers (2) students. The results showed that the form of social support carried out by the counseling guidance teacher to improve student learning discipline went well. Because the social support provided by guidance and counseling teachers was given in a directed and regular manner to students.